Modernization of Shibhul Iddah for Men Perspective Compilation of Islamic Law - Novalia, Sisca; Rachman Hakim, Arief (KnE Social Sciences, 2024)
Iddah is the mass or waiting time for an ex-wife who has been divorced by her ex-husband. Mass iddah applies to women who have been divorced or because her husband died at which time the ex-wife has not been allowed to remarry with another man. Masa Iddah here is meant as a form of respect, mourning, and tolerance to the deceased and family. Honouring someone who has contributed to his life is a good thing and is encouraged in Islam. In this ever-evolving age, the author sees how the implementation of ’iddah is also directed at men. Then it would be more beautiful if the law applied to both. This study will examine how the regulations on the mass of iddah for men that have been listed in the compilation of Islamic law are then connected to the point of view of Islamic jurisprudence. How the role of fiqh law delivers these regulations so that these regulations are considered applicable in Indonesia. The analysis method used is in the form of descriptive analysis by explaining what is meant by the theory of ’iddah, the compilation of Islamic law and Islamic jurisprudence. Furthermore, from this presentation, an analysis of the postulates that explain ’iddah is carried out. The analysis in question is to analyze the verse about ’iddah to be made into law and applied to men using the theory of compilation of Islamic law. Keywords: Shibhul ’Iddah male, compilation of Islamic law, interpretation